Contextualized Contribution of Kindness to Favorable Goal- and Circumstantial-Driven Neuropsychological Regulation - Mota, Nayara; Chaves, Elenilda; Antunes, Marina; Borges, Rudi; Paiva, Andressa; Santos, Vanessa (Frontiers in Psychology, 2017)
Kindness involves care and non-judgmental understanding towards someone. As a prosocial inclination, kindness would increase the possibility of favorable interaction with the environment, with a successful adjustment of one´s response in novel or challenging circumstances, taking into account rules or goals. This adjustment ability is commonly referred to as executive functions, dependent on the prefrontal and parietal functioning, still under development during late adolescence. This study aimed to investigate if kindness would relate with the executive functions. If so, it would correlate more with measures of self-regulation, mainly dependent on the medial prefrontal corticosubcortical circuits. Also, among self-regulating processes, kindness would be more associated with autonomic responses – choices guided by one's understanding/intention - than with adaptive responses - changes on one's choices triggered by unfavorable circumstances. A sample of 46 (31 female; 18 to 21 years-old) healthy college students from the University of the State of Rio de Janeiro attended a clinical interview and a comprehensive neuropsychological assessment. Kindness was measured by the Compassion Scale subscore. Generalized non-linear models for each neuropsychological variable were executed on R, followed by an estimation of weighted parameters for each factor. Significant models which included kindness (weighted parameter Pc > 74) and all of their psychosocial or sociodemographic factors on their maximum expression (Pc > 74) were identified. In a contextualized joint influence with other psychosocial and sociodemographic factors, kindness fits equally goal- and circumstantial- self-regulation, as well as integrative organization of information. Kindness is a principle that optimizes a refreshing and prosocial interaction with the environment. As it anticipates sharing and cooperation behaviors, it might have a primordial function on individual and social development.